Conductive container bag and preparation method thereof

By combining modified polypropylene and polyethylene, conductive flat wires including PA layer, adhesive layer and PP conductive layer were prepared, which solved the problems of unstable conductivity and insufficient service life of the conductive container bag, and achieved high efficiency , preparation of durable conductive container bags.

CN119411280APending Publication Date: 2025-02-11SHENZHEN JIANGTIAN PACKAGING MATERIALS CO LTD

Patent Information

Application Number
CN202411552609.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The conductive properties of conductive container bags are unstable under different environmental conditions, and lack service life and durability. Traditional preparation processes lead to waste of materials and high production costs.

Method used

The conductive flat wire including a PA layer, an adhesive layer and a PP conductive layer are used to improve the antistatic ability, tensile strength and impact resistance of the conductive flat wire through the combination of modified polypropylene and modified polyethylene.

Benefits of technology

It significantly improves the conductivity stability, service life and durability of conductive container bags, and reduces material waste and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411280A_ABST
    Figure CN119411280A_ABST
Patent Text Reader

Abstract

The invention provides a conductive container bag and a preparation method thereof. The preparation method comprises the following steps: (1) preparing a conductive flat wire, wherein the conductive flat wire comprises a PA layer, a bonding layer and a PP conductive layer; the two surfaces of the PA layer are respectively provided with a bonding layer, the other surface of each bonding layer is provided with a PP conductive layer, each bonding layer is co-extruded between the PA layer and the PP conductive layer, and the extrusion temperature is 240-250 DEG C; and (2) weaving: weaving by using conductive flat filaments to obtain the conductive container bag. Modified polypropylene is used as the PP conductive layer, and the PP conductive layer, the bonding layer and the PA layer have a synergistic effect, so that the conductivity and the mechanical strength of the conductive container bag can be synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of woven fabrics, and in particular relates to a conductive bulk bag and a preparation method thereof. Background Art

[0002] Conductive bulk bags, also known as static discharge bulk bags or anti-static bulk bags, are packaging containers specifically designed for handling and transporting dry bulk materials that may generate static electricity. These bulk bags are usually made of fabrics containing conductive materials or carbon threads, which can help disperse static charges, thereby reducing the risk of fire or explosion caused by static electricity accumulation.

[0003] Although conductive bulk bags are currently effective in preventing static electricity accumulation, they may encounter some technical problems in actual application, such as: Stability of conductive properties: The conductive properties of conductive bulk bags may be affected by environmental humidity. In a dry environment, the performance of the conductive thread may be weakened; in a high humidity environment, although the conductive properties may be enhanced, it may also cause the material to lose strength after absorbing moisture. Service life and durability: Since the conductive threads are usually embedded or sewn inside the container bag, they may wear or break over time, resulting in a decrease in conductive properties.

[0004] In the traditional conductive flat wire extrusion and drawing process, in order to balance the two mutually restrictive performance indicators of surface resistance and tensile strength, the common practice is to increase the thickness and width of the flat wire to improve its tensile strength. However, this method will lead to an increase in the elongation at break and weight of the single wire, resulting in a large amount of material waste. In addition, this method will also bring high production costs, as well as challenges in process repeatability and stability, which greatly limit the application effect and scope of conductive flat wire in conductive container bags. In other words, in the traditional process of preparing conductive flat wire, increasing the size of the flat wire in order to improve the tensile strength, although it solves the strength problem, it brings about problems such as material waste, rising costs, and difficulty in maintaining consistency and controllability of the production process, all of which constitute obstacles to the practical application of conductive flat wire in conductive container bags.

[0005] Therefore, there is an urgent need for a conductive bulk bag and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a conductive bulk bag and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a conductive bulk bag comprises the following steps:

[0009] (1) Preparing a conductive flat wire: The conductive flat wire comprises a PA layer, an adhesive layer and a PP conductive layer; the two surfaces of the PA layer are respectively provided with adhesive layers, and the other surface of each adhesive layer is provided with a PP conductive layer, and each adhesive layer is co-extruded between the PA layer and the PP conductive layer, and the extrusion temperature is 240-250° C.;

[0010] The material of the PP conductive layer is modified polypropylene; the modified polypropylene includes the following raw materials in parts by weight: 30-35 parts of polypropylene, 7-10 parts of modified filler, 2-6 parts of modified polyethylene, 1-1.5 parts of aluminate coupling agent, 1-2 parts of light stabilizer and 0.5-1.4 parts of antioxidant;

[0011] The preparation method of the modified filler comprises the following steps:

[0012] Step 1, mixing graphene, carbon black and double-walled carbon nanotubes in a weight ratio of (1.2-1.4): (0.5-0.7): 1 to obtain a mixed filler;

[0013] Step 2: Mix a mixed filler, nano zinc oxide, a silane coupling agent KH550 and an ethanol aqueous solution with a weight ratio of 1: (1.5-2): (0.03-0.05): (8-10), perform ultrasonic treatment at 20-30kHz for 1-2h, filter and dry to obtain a filler loaded with nano zinc oxide;

[0014] Step 3, mixing a filler loaded with nano zinc oxide, hexadecylamine, a silane coupling agent KH550 and water in a weight ratio of 1: (0.2-0.3): (0.1-0.2): (8-10), stirring at 40-45° C. for 40-50 min, heating to 85-90° C., stirring for 60-70 min, centrifuging and drying to obtain a modified filler;

[0015] (2) Weaving: Use conductive flat wire for weaving to obtain a conductive container bag.

[0016] Furthermore, the graphene sheet diameter is 0.5-5 μm and the specific surface area is 894 m 2 / g, pore size of 4.5-4.6nm, thickness of 3.2-4.2nm; purchased from Xianfeng Nano; the average primary particle size of carbon black is 30-45nm, and the specific surface area is 125m 2 / g, purchased from Xianfeng Nano; double-walled carbon nanotubes with a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g. Purchased from Xianfeng Nano.

[0017] The particle size of nano zinc oxide is 30-50nm and the specific surface area is 15-30m 2 / g. Zhejiang Zhitai Nano-Micro New Materials Co., Ltd.

[0018] Polypropylene has the characteristics of good flame retardancy and transparency, dimensional stability and strong recyclability, and is usually used as the raw material of conductive container bags. However, PP has a large resistance value, the product has poor water absorption, and is prone to static electricity. The present invention attempts to add conductive fillers to polypropylene materials, but the conductive fillers have poor compatibility with the components in the system and are prone to agglomeration. The present invention can improve the antistatic ability of the conductive flat yarn by modifying the mixture of three different conductive fillers. The three fillers have complementary advantages in physical and chemical properties, and can produce a synergistic effect, so that the overall conductive performance is better than that of a single filler. This synergistic effect can significantly improve the antistatic ability of the material, and the modified filler improves the dispersibility in the system, further enhancing the stability and conductive performance of the conductive network. At the same time, the addition of modified fillers in the present invention improves the tensile strength of the conductive flat yarn.

[0019] Further, the polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of (1.4-1.6): 1: (0.3-0.5), the melt index of polypropylene I is 3g / 10min (test method ISO1133), the elongation at break is 600% (ISO527); the rigidity coefficient is 1226MPa (ISO178), Taiwan Formosa Plastics, polypropylene homopolymer, model 1040F; the melt index of polypropylene II is 18 ... Method ISO1133), elongation at break is 300% (ISO527); rigidity coefficient is 1324MPa (ISO178), Formosa Plastics, Taiwan, China, polypropylene homopolymer, model 1202F; the melt index of polypropylene III is 3g / 10min (test method ISO1133), elongation at break is 500% (ISO527); rigidity coefficient is 490MPa (ISO178), Formosa Plastics, Taiwan, China, polypropylene random copolymer, model 5020.

[0020] Model 1040F polypropylene of Formosa Plastics of Taiwan, China is a commonly used bulk bag raw material, but the single-filament tension of the conductive bulk bag prepared by the present invention is not good. The present invention compounds three types of polypropylene to improve the single-filament tension of the conductive flat wire. By compounding polypropylenes with different properties, the best balance between strength, rigidity and flexibility of the material can be achieved, thereby improving the single-filament tension of the conductive flat wire; compounding polypropylenes with different properties can optimize the fluidity of the material, ensure the uniformity and density of the material during processing, reduce defects and gaps, and further improve the mechanical properties of the single wire.

[0021] Furthermore, the preparation method of modified polyethylene includes the following steps: mixing 100 parts of low-density polyethylene, 20-22 parts of urea-formaldehyde resin, 4-7 parts of silicone rubber curing agent, 6-9 parts of salicylic acid and 28-30 parts of ethanol by weight, adding them to an open mill, mixing and reacting at a temperature of 180-200°C for 1-2h, and extruding and granulating at a temperature of 220-240°C using an extruder to obtain modified polyethylene.

[0022] Urea-formaldehyde resin was purchased from Jinan Jinyu Chemical Co., Ltd., with a free formaldehyde content of 0.05 wt% and a viscosity of 0.25-0.4 Pa.s.

[0023] Furthermore, the low-density polyethylene comprises low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1: (0.2-0.4): (1.4-1.6); the low-density polyethylene I has a melt index of 0.3 g / 10 min and a density of 0.923 g / cm 3 , purchased from Maoming Petrochemical, model 2520D. The melt index of low-density polyethylene II is 1.0g / 10min, and the density is 0.920g / cm 3 , purchased from Formosa Plastics, Taiwan, China, model 3210. The melt index of low-density polyethylene III is 2.0 g / 10 min, and the density is 0.922 g / cm 3 , purchased from Formosa Plastics Corporation in Taiwan, China, model 3224D.

[0024] The present invention attempts to add polyethylene to the system to improve the impact resistance of the conductive flat wire, but the effect is not ideal. The present invention can improve the impact resistance of the conductive flat wire by modifying polyethylene. Urea-formaldehyde resin can improve the interface compatibility between polyethylene and polypropylene, enhance the bonding force between the two, and improve the impact resistance of the composite material; silicone rubber curing agent can promote the cross-linking reaction between polyethylene and urea-formaldehyde resin, form a more stable network structure, and improve the mechanical properties of the material.

[0025] During long-term use and storage, conductive bulk bags will be exposed to sunlight, air, humidity and other environments, which will cause aging of the material. Aging will reduce the tensile strength of the material, thereby affecting the service life and safety of the bulk bag. When fillers with specific parameters, polypropylene with specific parameters and polyethylene with specific parameters are used in the system of the present invention, the three can improve the tensile strength of the conductive flat wire under aging resistance conditions through synergistic effect, thereby increasing the service life of the conductive bulk bag.

[0026] Furthermore, the silicone rubber curing agent is dichloromethyltriethoxysilane, which is purchased from Hubei Kewode Chemical Co., Ltd.

[0027] Furthermore, the light stabilizer is light stabilizer 2020. Brand: BASF.

[0028] Furthermore, the antioxidant is antioxidant 245. Brand: BASF.

[0029] Furthermore, the material of the adhesive layer is maleic anhydride grafted EVA resin. Purchased from Arkema, France, model 18211.

[0030] Furthermore, the preparation method of the modified polypropylene comprises the following steps: mixing the components in a mixer, and then extruding and granulating them through a twin-screw extruder granulator, wherein the inlet temperature of the twin-screw extruder granulator is 240-245° C. and the outlet temperature is 160-170° C., to obtain the modified polypropylene.

[0031] Furthermore, the material of the PA layer is nylon 6. Manufacturer: Japan Ube, product name: PA6, brand: 1018I.

[0032] Further,

[0033] Furthermore, the thickness of each adhesive layer accounts for 3-4% of the total thickness of the conductive flat wire.

[0034] Furthermore, the thickness of each PP conductive layer accounts for 12-14% of the total thickness of the conductive flat yarn.

[0035] The invention also provides a conductive container bag prepared by the preparation method.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0037] 1. The present invention can improve the antistatic ability of the conductive flat wire by mixing and modifying three different conductive fillers; at the same time, adding the modified filler increases the tensile strength of the conductive flat wire.

[0038] 2. The present invention compounds three types of polypropylene to improve the single-filament tension of the conductive flat filament.

[0039] 3. The present invention can improve the impact resistance of the conductive flat wire by modifying the polyethylene.

[0040] 4. When fillers with specific parameters, polypropylene with specific parameters and polyethylene with specific parameters are used in the system of the present invention, the three can improve the tensile strength of the conductive flat wire under aging resistance conditions and increase the service life of the conductive container bag through synergistic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a physical picture of the conductive container bag prepared according to the present invention. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing a conductive container bag, comprising the following steps:

[0045] (1) Preparation of conductive flat yarn: The conductive flat yarn comprises a PA layer, an adhesive layer and a PP conductive layer; the two surfaces of the PA layer are provided with adhesive layers respectively, and the other surface of each adhesive layer is provided with a PP conductive layer, and each adhesive layer is co-extruded between the PA layer and the PP conductive layer, and the extrusion temperature is 245°C; the material of the adhesive layer is maleic anhydride grafted EVA resin. Purchased from Arkema, France, model 18211. The material of the PA layer is nylon 6. Manufacturer: Japan Ube, product name: PA6, brand: 1018I. The thickness of each adhesive layer accounts for 3.6% of the total thickness of the conductive flat wire. The thickness of each PP conductive layer accounts for 13% of the total thickness of the conductive flat wire.

[0046] (2) Weaving: Use conductive flat wire for weaving to obtain a conductive container bag.

[0047] The material of the PP conductive layer is modified polypropylene; the modified polypropylene includes the following raw materials in parts by weight: 32 parts of polypropylene, 9 parts of modified filler, 4 parts of modified polyethylene, 1.2 parts of aluminate coupling agent, 1.6 parts of light stabilizer and 0.8 parts of antioxidant;

[0048] The light stabilizer is light stabilizer 2020. Brand: BASF.

[0049] The antioxidant is antioxidant 245. Brand: BASF.

[0050] The preparation method of the modified filler comprises the following steps:

[0051] Step 1, mixing graphene, carbon black and double-walled carbon nanotubes in a weight ratio of 1.3:0.6:1 to obtain a mixed filler;

[0052] Step 2: Mix a mixed filler, nano zinc oxide, silane coupling agent KH550 and 65% ethanol aqueous solution in a weight ratio of 1:1.7:0.04:9, perform ultrasonic treatment at 25kHz for 1.6h, filter and dry to obtain a filler loaded with nano zinc oxide;

[0053] Step 3: Mix the nano zinc oxide loaded filler, hexadecylamine, silane coupling agent KH550 and water in a weight ratio of 1:0.25:0.16:9, stir at 42°C for 45 minutes, heat to 88°C, stir for 65 minutes, centrifuge and dry to obtain a modified filler;

[0054] The graphene sheet diameter is 0.5-5 μm and the specific surface area is 894 m 2 / g, pore size of 4.5-4.6nm, thickness of 3.2-4.2nm; purchased from Xianfeng Nano; the average primary particle size of carbon black is 30-45nm, and the specific surface area is 125m 2 / g, purchased from Xianfeng Nano; double-walled carbon nanotubes with a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g. Purchased from Xianfeng Nano.

[0055] The particle size of nano zinc oxide is 30-50nm and the specific surface area is 15-30m 2 / g. Zhejiang Zhitai Nano-Micro New Materials Co., Ltd.

[0056] Polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of 1.5:1:0.4. The melt index of polypropylene I is 3g / 10min (test method ISO1133), and the elongation at break is 600% (ISO527); the rigidity coefficient is 1226MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1040F; the melt index of polypropylene II is 18g / 10min (test method ISO1133), and the elongation at break is 300% (ISO527); the rigidity coefficient is 1324MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1202F; the melt index of polypropylene III is 3g / 10min (test method ISO1133), and the elongation at break is 500% (ISO527); the rigidity coefficient is 490MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene random copolymer, model 5020.

[0057] The preparation method of modified polyethylene includes the following steps: 100 parts of low-density polyethylene, 21 parts of urea-formaldehyde resin, 6 parts of silicone rubber curing agent, 8 parts of salicylic acid and 29 parts of ethanol are mixed by weight, added into an open mill, mixed and reacted at a temperature of 190° C. for 1.6 hours, and extruded and granulated by an extruder at a temperature of 230° C. to obtain modified polyethylene.

[0058] Urea-formaldehyde resin was purchased from Jinan Jinyu Chemical Co., Ltd., with a free formaldehyde content of 0.05 wt% and a viscosity of 0.25-0.4 Pa.s. The silicone rubber curing agent was dichloromethyl triethoxysilane, purchased from Hubei Kewode Chemical Co., Ltd.

[0059] The low-density polyethylene comprises low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1:0.3:1.5; the low-density polyethylene I has a melt index of 0.3 g / 10 min and a density of 0.923 g / cm 3 , purchased from Maoming Petrochemical, model 2520D. The melt index of low-density polyethylene II is 1.0g / 10min, and the density is 0.920g / cm 3 , purchased from Formosa Plastics, Taiwan, China, model 3210. The melt index of low-density polyethylene III is 2.0 g / 10 min, and the density is 0.922 g / cm 3 , purchased from Formosa Plastics Corporation in Taiwan, China, model 3224D.

[0060] The preparation method of the modified polypropylene comprises the following steps: mixing the components in a mixer, and then extruding and granulating the components through a twin-screw extruder granulator, wherein the inlet temperature of the twin-screw extruder granulator is 242° C. and the outlet temperature is 165° C., to obtain the modified polypropylene.

[0061] Example 2

[0062] This embodiment provides a method for preparing a conductive container bag, comprising the following steps:

[0063] (1) Preparation of conductive flat yarn: The conductive flat yarn comprises a PA layer, an adhesive layer and a PP conductive layer; the two surfaces of the PA layer are provided with adhesive layers respectively, and the other surface of each adhesive layer is provided with a PP conductive layer, and each adhesive layer is co-extruded between the PA layer and the PP conductive layer, and the extrusion temperature is 240°C; the material of the adhesive layer is maleic anhydride grafted EVA resin. Purchased from Arkema, France, model 18211. The material of the PA layer is nylon 6. Manufacturer: Japan Ube, product name: PA6, brand: 1018I. The thickness of each adhesive layer accounts for 3% of the total thickness of the conductive flat wire. The thickness of each PP conductive layer accounts for 14% of the total thickness of the conductive flat wire.

[0064] (2) Weaving: Use conductive flat wire for weaving to obtain a conductive container bag.

[0065] The material of the PP conductive layer is modified polypropylene; the modified polypropylene includes the following raw materials in parts by weight: 30 parts of polypropylene, 10 parts of modified filler, 2 parts of modified polyethylene, 1.5 parts of aluminate coupling agent, 1 part of light stabilizer and 1.4 parts of antioxidant;

[0066] The light stabilizer is light stabilizer 2020. Brand: BASF.

[0067] The antioxidant is antioxidant 245. Brand: BASF.

[0068] The preparation method of the modified filler comprises the following steps:

[0069] Step 1, mixing graphene, carbon black and double-walled carbon nanotubes in a weight ratio of 1.2:0.7:1 to obtain a mixed filler;

[0070] Step 2: Mix a mixed filler, nano zinc oxide, a silane coupling agent KH550 and an ethanol aqueous solution with a weight ratio of 1:1.5:0.03:10, perform ultrasonic treatment at 20kHz for 1 hour, filter and dry to obtain a filler loaded with nano zinc oxide;

[0071] Step 3: Mix the nano zinc oxide loaded filler, hexadecylamine, silane coupling agent KH550 and water in a weight ratio of 1:0.2:0.1:8, stir at 45°C for 40 minutes, heat to 90°C, stir for 60 minutes, centrifuge and dry to obtain a modified filler;

[0072] The graphene sheet diameter is 0.5-5 μm and the specific surface area is 894 m 2 / g, pore size of 4.5-4.6nm, thickness of 3.2-4.2nm; purchased from Xianfeng Nano; the average primary particle size of carbon black is 30-45nm, and the specific surface area is 125m 2 / g, purchased from Xianfeng Nano; double-walled carbon nanotubes with a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g. Purchased from Xianfeng Nano.

[0073] The particle size of nano zinc oxide is 30-50nm and the specific surface area is 15-30m 2 / g. Zhejiang Zhitai Nano-Micro New Materials Co., Ltd.

[0074] Polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of 1.6:1:0.3. The melt index of polypropylene I is 3g / 10min (test method ISO1133), and the elongation at break is 600% (ISO527); the rigidity coefficient is 1226MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1040F; the melt index of polypropylene II is 18g / 10min (test method ISO1133), and the elongation at break is 300% (ISO527); the rigidity coefficient is 1324MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1202F; the melt index of polypropylene III is 3g / 10min (test method ISO1133), and the elongation at break is 500% (ISO527); the rigidity coefficient is 490MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene random copolymer, model 5020.

[0075] The preparation method of modified polyethylene comprises the following steps: 100 parts of low-density polyethylene, 20 parts of urea-formaldehyde resin, 7 parts of silicone rubber curing agent, 6 parts of salicylic acid and 30 parts of ethanol are mixed by weight, added into an open mill, mixed and reacted at a temperature of 200° C. for 2 hours, and extruded and granulated by an extruder at a temperature of 240° C. to obtain modified polyethylene.

[0076] Urea-formaldehyde resin was purchased from Jinan Jinyu Chemical Co., Ltd., with a free formaldehyde content of 0.05 wt% and a viscosity of 0.25-0.4 Pa.s. The silicone rubber curing agent was dichloromethyl triethoxysilane, purchased from Hubei Kewode Chemical Co., Ltd.

[0077] The low-density polyethylene comprises low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1:0.4:1.4; the low-density polyethylene I has a melt index of 0.3 g / 10 min and a density of 0.923 g / cm 3 , purchased from Maoming Petrochemical, model 2520D. The melt index of low-density polyethylene II is 1.0g / 10min, and the density is 0.920g / cm 3 , purchased from Formosa Plastics, Taiwan, China, model 3210. The melt index of low-density polyethylene III is 2.0 g / 10 min, and the density is 0.922 g / cm 3 , purchased from Formosa Plastics Corporation in Taiwan, China, model 3224D.

[0078] The preparation method of the modified polypropylene comprises the following steps: mixing the components in a mixer, and then extruding and granulating them through a twin-screw extruder granulator, wherein the inlet temperature of the twin-screw extruder granulator is 240° C. and the outlet temperature is 170° C., to obtain the modified polypropylene.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 1 is that graphene, carbon black and double-walled carbon nanotubes are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the graphene sheet diameter is 4-9 μm and the specific surface area is 587 m 2 / g, pore size of 4.7-4.9nm, thickness of 4.5-5.0nm; purchased from Xianfeng Nano; the average primary particle size of carbon black is 50-75nm, and the specific surface area is 86m 2 / g, purchased from Xianfeng Nano; double-walled carbon nanotubes have a diameter of 3-6nm, a length of 1-4μm, and a specific surface area of ​​210m 2 / g. Purchased from Xianfeng Nano.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 1 is that the polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of 1:1:1, the melt index of polypropylene I is 3g / 10min (test method ISO1133), and the elongation at break is 600% (ISO527); the rigidity coefficient is 1226MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, a polypropylene homopolymer, model 1040F; the melt index of polypropylene II is 18g / 10min (test method ISO1133), and the elongation at break is 300% (ISO527); the rigidity coefficient is 1324MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, a polypropylene homopolymer, model 1202F; the melt index of polypropylene III is 3g / 10min (test method ISO1133), and the elongation at break is 500% (ISO527); the rigidity coefficient is 490MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, a polypropylene random copolymer, model 5020.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 1 is that the polypropylene is Formosa Plastics Corporation of Taiwan, China, a polypropylene homopolymer, model 1202F; the melt index is 3g / 10min (test method ISO1133), the elongation at break is 600% (ISO527); and the rigidity coefficient is 1226MPa (ISO178).

[0087] Comparative Example 5

[0088] The difference between this comparative example and Example 1 is that the polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of 1.5:1:0.4, the melt index of polypropylene I is 3g / 10min (test method ISO1133), and the elongation at break is 600% (ISO527); the rigidity coefficient is 1226MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1040F; the melt index of polypropylene II is 10g / 10min (test method ISO1133), and the elongation at break is 500% (ISO527); the rigidity coefficient is 1373MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene homopolymer, model 1080; the melt index of polypropylene III is 15g / 10min (test method ISO1133), and the elongation at break is 100% (ISO527); the rigidity coefficient is 1569MPa (ISO178), Formosa Plastics Corporation of Taiwan, China, polypropylene random copolymer, model 1120.

[0089] Comparative Example 6

[0090] The difference between this comparative example and Example 1 is that the polyethylene is not modified. The polyethylene is a low-density polyethylene, including low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1:0.3:1.5; the low-density polyethylene I has a melt index of 0.3 g / 10 min and a density of 0.923 g / cm 3 , purchased from Maoming Petrochemical, model 2520D. The melt index of low-density polyethylene II is 1.0g / 10min, and the density is 0.920g / cm 3 , purchased from Formosa Plastics, Taiwan, China, model 3210. The melt index of low-density polyethylene III is 2.0 g / 10 min, and the density is 0.922 g / cm 3 , purchased from Formosa Plastics Corporation in Taiwan, China, model 3224D.

[0091] Comparative Example 7

[0092] The difference between this comparative example and Example 1 is that the low-density polyethylene comprises low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1:1:1; the melt index of the low-density polyethylene I is 0.3 g / 10 min, and the density is 0.923 g / cm 3 , purchased from Maoming Petrochemical, model 2520D. The melt index of low-density polyethylene II is 1.0g / 10min, and the density is 0.920g / cm 3 , purchased from Formosa Plastics, Taiwan, China, model 3210. The melt index of low-density polyethylene III is 2.0 g / 10 min, and the density is 0.922 g / cm 3 , purchased from Formosa Plastics Corporation in Taiwan, China, model 3224D.

[0093] Performance Testing

[0094] The conductive flat yarns (single yarn width 4 mm, single yarn weight 9.8 g / 100 m) prepared in Examples 1-2 and Comparative Examples 1-7 were subjected to tensile (test standard ISO527-2), bending (test standard ISO178), impact (test standard ISO180), and surface resistance (test standard GB / T35513.2-2017) tests, and an aging experiment was carried out at the same time: the aging experiment was carried out for 1000 h at a relative humidity of 85°C and 85% RH, and the tensile strength retention rate after aging was determined as follows: tensile strength after aging / tensile strength after aging*100%.

[0095] The results are shown in Table 1.

[0096] Table 1 Performance test results

[0097]

[0098] It can be seen from the above performance test results that the conductive flat wires of Examples 1-2 have excellent comprehensive performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the raw materials.

[0099] The comparative examples, however, are significantly inferior to the embodiments in terms of the corresponding performance tests because the necessary technical solutions are not adopted. The ratios of the three fillers in comparative example 1 are different. It can be seen that the surface resistance becomes higher, the conductivity decreases, and the tensile strength of the conductive flat wire also decreases. The parameters of the fillers in comparative example 2 are changed, resulting in a decrease in the aging resistance of the conductive flat wire. The ratios of polypropylene in comparative example 3 are different. Comparative example 4 uses a single type of polypropylene. Comparative example 5 uses other types of polypropylene and polypropylene of model 1040F. It can be seen that the single-filament tension of the conductive flat wire has decreased to varying degrees, and the tensile strength of the conductive flat wire under aging resistance conditions has also decreased. In comparative example 6, polyethylene is not modified, and the impact resistance of the conductive flat wire decreases. The ratios of low-density polyethylene in comparative example 7 are different, and the tensile strength of the conductive flat wire under aging resistance conditions decreases. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a conductive container bag, characterized in that: The following steps are involved: (1) Preparing a conductive flat wire: The conductive flat wire comprises a PA layer, an adhesive layer and a PP conductive layer; the two surfaces of the PA layer are respectively provided with adhesive layers, and the other surface of each adhesive layer is provided with a PP conductive layer, and each adhesive layer is co-extruded between the PA layer and the PP conductive layer, and the extrusion temperature is 240-250° C.; The material of the PP conductive layer is modified polypropylene; the modified polypropylene includes the following raw materials in parts by weight: 30-35 parts of polypropylene, 7-10 parts of modified filler, 2-6 parts of modified polyethylene, 1-1.5 parts of aluminate coupling agent, 1-2 parts of light stabilizer and 0.5-1.4 parts of antioxidant; The preparation method of the modified filler comprises the following steps: Step 1, mixing graphene, carbon black and double-walled carbon nanotubes in a weight ratio of (1.2-1.4): (0.5-0.7): 1 to obtain a mixed filler; Step 2: Mix a mixed filler, nano zinc oxide, a silane coupling agent KH550 and an ethanol aqueous solution with a weight ratio of 1: (1.5-2): (0.03-0.05): (8-10), perform ultrasonic treatment at 20-30kHz for 1-2h, filter and dry to obtain a filler loaded with nano zinc oxide; Step 3, mixing a filler loaded with nano zinc oxide, hexadecylamine, a silane coupling agent KH550 and water in a weight ratio of 1: (0.2-0.3): (0.1-0.2): (8-10), stirring at 40-45° C. for 40-50 min, heating to 85-90° C., stirring for 60-70 min, centrifuging and drying to obtain a modified filler; (2) Weaving: Use conductive flat wire for weaving to obtain a conductive container bag.

2. The method for preparing a conductive container bag according to claim 1, characterized in that: The graphene sheet diameter is 0.5-5 μm and the specific surface area is 894 m 2 / g, pore size is 4.5-4.6nm, thickness is 3.2-4.2nm; the average primary particle size of carbon black is 30-45nm, and the specific surface area is 125m 2 / g; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g.

3. The method for preparing a conductive container bag according to claim 1, characterized in that: Polypropylene includes polypropylene I, polypropylene II and polypropylene III in a weight ratio of (1.4-1.6):1:(0.3-0.5), the melt index of polypropylene I is 3g / 10min, the elongation at break is 600%; the rigidity coefficient is 1226MPa; the melt index of polypropylene II is 18g / 10min, the elongation at break is 300%; the rigidity coefficient is 1324MPa; the melt index of polypropylene III is 3g / 10min, the elongation at break is 500%; the rigidity coefficient is 490MPa.

4. The method for preparing a conductive container bag according to claim 1, characterized in that: The preparation method of modified polyethylene comprises the following steps: 100 parts of low-density polyethylene, 20-22 parts of urea-formaldehyde resin, 4-7 parts of silicone rubber curing agent, 6-9 parts of salicylic acid and 28-30 parts of ethanol are mixed by weight, added into an open mill, mixed and reacted at a temperature of 180-200° C. for 1-2 hours, extruded and granulated by an extruder at a temperature of 220-240° C. to obtain modified polyethylene.

5. The method for preparing a conductive container bag according to claim 4, characterized in that: The low-density polyethylene comprises low-density polyethylene I, low-density polyethylene II and low-density polyethylene III in a weight ratio of 1: (0.2-0.4): (1.4-1.6); the low-density polyethylene I has a melt index of 0.3 g / 10 min and a density of 0.923 g / cm 3 ; The melt index of low-density polyethylene II is 1.0g / 10min and the density is 0.920g / cm 3 ; The melt index of low-density polyethylene III is 2.0g / 10min and the density is 0.922g / cm 3 .

6. The method for preparing a conductive bulk bag according to claim 4, characterized in that: The silicone rubber curing agent is dichloromethyltriethoxysilane.

7. The method for preparing a conductive bulk bag according to claim 1, characterized in that: The preparation method of the modified polypropylene comprises the following steps: mixing the components in a mixer, and then extruding and granulating them through a twin-screw extruder granulator, wherein the inlet temperature of the twin-screw extruder granulator is 240-245° C. and the outlet temperature is 160-170° C., to obtain the modified polypropylene.

8. The method for preparing a conductive bulk bag according to claim 1, characterized in that: The material of the PA layer is nylon 6; the material of the adhesive layer is maleic anhydride grafted EVA resin.

9. The method for preparing a conductive bulk bag according to claim 1, characterized in that: The thickness of each adhesive layer accounts for 3-4% of the total thickness of the conductive flat wire; the thickness of each PP conductive layer accounts for 12-14% of the total thickness of the conductive flat wire.

10. A conductive container bag made according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anti-electrostatic plastic woven bag and preparation method therefor

    CN106479043A

  • High-strength conductive PP / MLLDPE plastics for flat yarns and preparation method for high-strength conductive PP / MLLDPE plastics

    CN108586926A

  • Preparation method of urea-formaldehyde resin modified polyethylene

    CN109021353A

  • Light high-toughness conductive polypropylene composite material, and preparation method and application thereof

    CN110256768A

  • Preparation method of functionalized graphene modified ABS (Acrylonitrile Butadiene Styrene) composite material

    CN118459925A

Cited By

  • Multilayer composite conductive flat filament, fabric and production process

    CN119877147A